LUDICIDADE AND PEDAGOGICAL MEDIATION IN THE PERTAINING TO SCHOOL PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
The current educational context imposes the necessity of significant changes in the education system in that if it relates to the constitution of new positionings of the professor in relation to the metodológicas strategies. Thus, the quarrels on the pertaining to school physical education evidence the concern with the construction to know corporal and the corporal performance of the pupils in relation to the corporeidade. The objective of this research was to investigate where measured the development of playful activities in the lessons of physical education they can contribute for education learning of the pupils of the basic education, thus identifying, the paper of the professor in this context and contributions of these activities for the adolescent child/. It consists of the development of a qualitative research on the ludicidade as base of metodológicas strategies in the lessons of physical education and the paper of the professor in this context, counting on a study on practical the pedagogical ones of disciplines of physical education in the pertaining to school context. In the interventions carried through for the development of the research activities had been specifically developed that make possible the rescue of the playful activities in the context of the lessons of physical education. E the data had been collected by means of comments guided for daily of field, informal, plain interviews of action and attended interventions that, had been analyzed in its qualitative dimension.
Keywords: Pertaining to school Physical education; Ludicidade; Pedagogical mediation